DIGITAL COPYWRITING ELEMENTS IN TAYLOR SWIFT'S 'FOLKLORE' ALBUM ON INSTAGRAM - Moluscas, Vergina; Alfin Rosyidha (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
The digital music industry has undergone transformative changes in the last decades, evolving from physical sales dominance to streaming supremacy. This evolution has fundamentally altered not only how music is consumed but also how it is marketed and promoted. In this study, the researcher focuses on how Taylor Swift worked on her album called ‘folklore’. To examine how the copywriting approach for ‘folklore’ represents an evolution in Taylor Swift’s marketing strategy compared to her previous albums, and identify how copywriting formulas were strategically implemented on Instagram promotional platforms for the ‘folklore’ album. This study applies a qualitative approach that allows the researcher to explore Swift’s work while acknowledging the understanding in discourse analysis in digital copywriting. Taylor Swift applied many copywriting approaches, including liking, scarcity, authority, future pacing, and consistency, combined with structured formulas such as AIDA, Before-After-Bridge, 4Cs, and SELWAB. Otherwise, the AIDA Formula and Consistency Approach dominate the copywriting elements of Taylor Swift’s.